How to Reform Business Inspections : Design, Implementation, Challenges - Blanc, Florentin; Leseur, Marielle (International Finance Corporation, Washington, DC, 2016)
Business inspections reform is part of a broader set of products and approaches the World Bank Group Investment Climate Advisory Services uses to improve business regulations, in particular relating to start-up and operation. These products cover such complementary issues as business registration and start-up procedures, licensing and permit practices, inspection procedures, and enforcement. This handbook should take its place alongside the World Bank Group’s (WBG) 2009 guide on How To Reform Business Licenses. It aims to provide would-be reformers, inside and outside of the WBG, with a comprehensive range of tools that enable them to tackle all essential aspects of regulatory simplification and smarter regulation. It also builds on earlier work the WBG has done on inspections reform, particularly on a number of reform projects the WBG has worked on since the late 1990s, and on a set of knowledge management publications the WBG has produced, most importantly the toolkit Good Practices for Business Inspections, Guidelines for Reformers (2006). Other important WBG publications on inspections reform include sets of case studies and overviews of country experiences (in particular a review of international experience published in 2005), a manual on checklist development (2009), and a note on assessment tools for inspections (2009). To keep reformers abreast of the latest developments in good practice, this handbook should be followed up by further reviews of international experience.